Assessment of Solid Waste Management at Source in Compliance With Guidelines Among Residents of Kawempe Division, Kampala, Uganda - Maderu, Paul; Omona, Kizito (Researchsquare, 2021)
Solid waste management poses a big challenge for many urban households, municipalities and cities, especially in developing countries, partly due to increasing urbanization. Overcrowding and informal settlements have emerged with illegal and indiscriminate waste disposal. Guidelines for proper management of solid waste are least observed at house hold level in such settings. The purpose of the study was to assess solid waste management at source in compliance with guidelines among residents of Kawempe municipality Kampala district. It was descriptive and analytical cross-sectional study design, with both quantitative and qualitative methods. 385 households heads and four local leaders were interviewed using researcher administered questionnaires and interview guide. The study found that only 37.9% of households complied with guidelines for solid waste management at source. Factors of waste management practices were waste reduction (p=0.005), separation (p=0.001), reuse (p=0.001) and composting (p=0.027). Determinants such as gender (p=0.007), marital status (p=0.016), level of education (p<0.0001), occupation (p=0.007), household size (p=0.025),medium of community sensitization (p<0.0001), enforcement of bi-laws (p=0.005), type of waste generated (p<0.0001) and waste storage method (p=0.009) were implicated. Compliance with guidelines in the management of household solid waste at source was still very low within the city. Authorities ought to intensify household solid waste management awareness campaigns.
Keywords: : Solid waste management, Compliance, Guidelines, Kampala, Uganda